The World Heritage Convention, the environment, and compliance - Goodwin, Edward J. (University Press of Colorado for CJIELP, 2009)
This Article highlights a particular strength of the World Heritage Convention within the international environmental law project that enhances conservation of natural areas, flora, and fauna. This strength relates to the World Heritage Convention’s ability to pull states towards meaningful compliance with obligations connected to protecting, conserving, presenting, and transferring to future generations the world’s natural (and cultural) heritage.